Sistem Pendukung Keputusan dalam Pemilihan Jasa Kurir Terbaik Menggunakan Metode AHP-WASPAS - Majid, Dzikri Fauzul; Wibisono, Setyawan (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
This research aims to develop a decision support system to assist in selecting the best courier service based on specific criteria. The applied method involves using the Analytical Hierarchy Process (AHP) combined with the Weighted Aggregated Sum Product Assessment (WASPAS) method to ensure accuracy in choosing the criteria for selecting the best courier service. The criteria used in this research for selecting a courier service include delivery cost, delivery speed, number of branches, and service quality. The AHP method is utilized to generate relative weight values for each criterion, while the WASPAS method is employed to calculate the final scores for courier services based on the predetermined weights. The research results provide recommendations for selecting the best courier service. System testing results indicate that the AHP and WASPAS methods can offer more accurate suggestions in courier service selection, leading to optimal outcomes